STUDI PENELUSURAN TUGAS DAN KINERJA ALUMNI STPP MAGELANG JURUSAN PENYULUHAN PERTANIAN YOGYAKARTA (THE TRACER STUDY OF THE STPP MAGELANG GRADUATES TASKS AND PERFORMANCES FOR AGRICULTURAL EXTENSION PROGRAM STUDY) - Arifin, Miftakhul; Ismarlin, Ina Fitria; Iswardayati, Nani Tri; Hamid, Abdul (Jurnal Ilmu-Ilmu Pertanian, 2008)
This study aimed at revealing the graduates working as Agricultural Extension Workers (AEWs), graduate performance condition, and the correlation between the performance and Cummulative Achievement Index (CAI). This study was descriptive in nature involving the graduates as objects, and the respondents i.e. the graduate leaders, the graduate partnerships, and farmer group leaders. The data collected by questioner and documentation methods, and analyzed by descriptive technique and Kendalls Tau Correlation Test. The result of studies are as follows, (1) 50% of all the graduates worked as AEWs, (2) the graduates job performance falls into the successful category, especially the action aspect is in the mostly successful category, (3) the graduates attitude is in the best category, especially the enthusiasm aspect is in the good category, (4) there is significant correlation between the graduates job performance and Cummulative Achievement Index (CAI), and (5) ) there is no significant correlation between the graduates attitude performance and Cummulative Achievement Index (CAI). This implies that there is a need of evaluation and development of the curriculum, and partnership between STPP and stakeholders so that the curriculum is relevant and applicable to the graduates job descriptions as AEWs.